Effects of Acetylcholine and Noradrenalin on Action Potentials of Isolated Rabbit Sinoatrial and Atrial Myocytes - Verkerk, Arie O.; Geuzebroek, Guillaume S.; Veldkamp, Marieke W.; Wilders, Ronald (Frontiers in Physiology, 2012)
The autonomic nervous system controls heart rate and contractility through sympathetic and parasympathetic inputs to the cardiac tissue, with acetylcholine (ACh) and noradrenalin (NA) as the chemical transmitters. In recent years, it has become clear that specific Regulators of G protein Signalling proteins (RGS proteins) suppress muscarinic sensitivity and parasympathetic tone, identifying RGS proteins as intriguing potential therapeutic targets. In the present study, we have identified the effects of 1 µM ACh and 1 µM NA on the intrinsic action potentials of sinotrial (SA) nodal and atrial myocytes. Single cells were enzymatically isolated from the SA node or from the left atrium of rabbit hearts. Action potentials were recorded using the amphotericin-perforated patch-clamp technique in the absence and presence of ACh, NA or a combination of both. In SA nodal myocytes, ACh increased cycle length and decreased diastolic depolarization rate, whereas NA decreased cycle length and increased diastolic depolarization rate. Both ACh and NA increased maximum upstroke velocity. Furthermore, ACh hyperpolarized the maximum diastolic potential. In atrial myocytes stimulated at 2 Hz, both ACh and NA hyperpolarized the maximum diastolic potential, increased the action potential amplitude, and increased the maximum upstroke velocity. Action potential duration at 50 and 90% repolarization was decreased by ACh, but increased by NA. The effects of both ACh and NA on action potential duration showed a dose dependence in the range of 1–1,000 nM, while a clear-cut frequency dependence in the range of 1–4 Hz was absent. Intermediate results were obtained in the combined presence of ACh and NA in both SA nodal and atrial myocytes. Our data uncover the extent to which SA nodal and atrial action potentials are intrinsically dependent on ACh, NA or a combination of both and may thus guide further experiments with RGS proteins.